Tissue Engineered Strategies for Skeletal Muscle Injury - Umile Giuseppe Longo; Mattia Loppini; Alessandra Berton; Filippo Spiezia; Nicola Maffulli; Vincenzo Denaro (Hindawi Limited, 2012)
Skeletal muscle injuries are common in athletes, occurring with direct and indirect mechanisms and marked residual effects, such as severe long-term pain and physical disability. Current therapy consists of conservative management including RICE protocol (rest, ice, compression, and elevation), nonsteroidal anti-inflammatory drugs, and intramuscular corticosteroids. However, current management of muscle injuries often does not provide optimal restoration to preinjury status. New biological therapies, such as injection of platelet-rich plasma and stem-cell-based therapy, are appealing. Although some studies support PRP application in muscle-injury management, reasons for concern persist, and further research is required for a standardized and safe use of PRP in clinical practice. The role of stem cells needs to be confirmed, as studies are still limited and inconsistent. Further research is needed to identify mechanisms involved in muscle regeneration and in survival, proliferation, and differentiation of stem cells.